2020
DOI: 10.1186/s12890-020-01275-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic characteristics of sputum and bronchoalveolar lavage fluid samples from patients with lower respiratory tract infection in a large teaching hospital in China: a retrospective study

Abstract: Background Lower respiratory tract infection (LRIs) is very common both in terms of community-acquired infection and hospital-acquired infection. Sputum and bronchoalveolar lavage fluid (BALF) are the most important specimens obtained from patients with LRI. The choice of antibiotic with which to treat LRI usually depends on the antimicrobial sensitivity of bacteria isolated from sputum and BALF. However, differences in the antimicrobial sensitivity of pathogens isolated from sputum and BALF have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…We found that 16 genera were depleted in sputum samples of the NSCLC group ( Fig. 3A ); both Neisseria and Fusobacterium were the dominant genera in the lung microbiota ( 13 ). These results confirmed that the sputum microbiome had been significantly altered in patients.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We found that 16 genera were depleted in sputum samples of the NSCLC group ( Fig. 3A ); both Neisseria and Fusobacterium were the dominant genera in the lung microbiota ( 13 ). These results confirmed that the sputum microbiome had been significantly altered in patients.…”
Section: Resultsmentioning
confidence: 93%
“…Huang et al compared the microbiotas of the lung (bronchoalveolar fluid) and sputum in LC patients and found similarly dominant taxonomic entities (taxa) at both phylum (such as Firmicutes , Bacteroidetes , Proteobacteria , Actinobacteria , and Fusobacteria ) and genus (such as Streptococcus , Prevotella , Neisseria , Porphyromonas , Veillonella , and Haemophilus ) levels, although some taxa might show significantly different abundances between the two microbiotas ( 12 ). In addition, Zheng et al compared the pathogens isolated from lung (bronchoalveolar fluid) and sputum and found that the top 10 most abundant ones were identical in both types of samples ( 13 ). Together, these studies suggest that sputum could be used as a close proxy for the lung.…”
Section: Introductionmentioning
confidence: 99%
“…Though they are also used for pathogen detection, their value in detecting causative pathogen is also unclear. A simple comparison of sputum culture and BALF culture was made in some studies, but the agreement between these two methods was seldom analyzed [ 10 , 11 ]. Few studies assessing the diagnostic accuracy of BGS used BALF culture as the reference standard.…”
Section: Introductionmentioning
confidence: 99%
“…Infectious diseases remain the leading cause of morbidity and mortality around the world [ 1 ].The lung infection, the most common infectious disease, has attracted wide concern, especially when it occurs in the form of explosive emerging infectious diseases such as severe acute respiratory syndrome (SARS) and coronavirus disease 2019 (COVID-19) [ 2 , 3 ]. However, some specific pulmonary infectious diseases should not be ignored.…”
Section: Introductionmentioning
confidence: 99%